Capturing the student user experience (UX) in York and Loughborough University Library buildings. Issue 2 (11th July 2016) - Burn, Katie; Cunningham, Matthew; Waller, Liz; Walton, Emma; Walton, Graham
Abstract : Purpose: – In higher education libraries, the concept of the user experience has increased in profile and importance. The concept of the "student as customer" has generated much debate but there is general agreement that universities need to be more successful in meeting student expectations. A key strategic area for university libraries has been to adapt and improve their physical spaces to ensure that they are still relevant for today's students. York and Loughborough University Libraries have both undergone building refurbishments and both are committed to monitoring and reviewing services and spaces. The paper aims to discuss these issues. Design/methodology/approach: – There were various constraints which very much influenced the methodology. These included: avoiding survey overload no resource allocation an acknowledgement that the methodology employed needed to combine rigour and validity with a pragmatic approach to data collection. A joint project team was established of representatives from each university. A questionnaire created on Google Forms was administered by staff with individuals in the library and entering the data onto a iPad. Findings: – Findings provide evidence of use across a range of users along with valuable information on who is using our library spaces and for what purpose. Originality/value: – This research is a rich contribution to the evidence based around student's learning in universities. It benefits from the expertise and knowledge of two university libraries. As university's continue to develop learning spaces, this work will enable further investigation around what makes a successful learning space and what makes the library a destination of choice.